An mRNA sequence derived from the yeast EST3 gene stimulates programmed +1 translational frameshifting - Taliaferro, Dwayne (Cold Spring Harbor Laboratory Press, 2007)
Programmed translational frameshift sites are sequences in mRNAs that promote frequent stochastic changes in translational reading frame allowing expression of alternative forms of protein products. The EST3 gene of Saccharomyces cerevisiae, encoding a subunit of telomerase, uses a programmed +1 frameshift site in its expression. We show that the site is complex, consisting of a heptameric sequence at which the frameshift occurs and a downstream 27-nucleotide stimulator sequence that increases frameshifting eightfold. The stimulator appears to be modular, composed of at least three separable domains. It increases frameshifting only when ribosomes pause at the frameshift site because of a limiting supply of a cognate aminoacyl-tRNA and not when pausing occurs at a nonsense codon. These data suggest that the EST3 stimulator may modulate access by aminoacyl-tRNAs to the ribosomal A site by interacting with several targets in a ribosome paused during elongation.